THERAPEUTIC PHYSICAL EDUCATION AND MASSAGE FOR SPINE DEFORMATION DURING PRACTICE (Physical Culture and Sport: Scientific Perspective, 2023)
The problem of youth health is key to quality education. Health is the main resource for everyday life, the fundamental and driving force of a young person's existence. Against this background, the search for ways to improve the state of health, increase physical capacity, and increase the functional capabilities of the body of those seeking education is of particular importance.The practical training of students majoring in "Secondary Education (Physical Culture)" requires constant expansion of the educational and practical base and improvement of students' professional skills regarding the development and implementation of a kinesitherapeutic program for the prevention of spinal deformities in children's postures. The purpose of this work is to diagnose spinal deformities in children's institutions and expand the professional competence of students in order to increase the physical activity of children by conducting physical therapy and massage. The modern way of life and reduced motor activity are factors that contribute to the occurrence of incorrect posture, various deformations of the spine and chest.The impact of physical therapy on reducing forced rest, improving tone and activating the body's activity, activating and improving the immune system, serves as a prevention of complications, restores and expands the capabilities of the child's body, accelerates recovery, and shortens the duration of treatment. Choosing special exercises, necessarily dosing them, depending on the nature and clinical course of the disease, it is possible to clearly influence and purposefully change certain functions of the schoolboy's body by restoring damaged systems, adapt the child to physical loads of a domestic and industrial nature
Keywords: therapeutic physical culture; massage; training; professional activity; prevention; sports; spinal deformities; healthy lifestyle